An Environment-Friendly and Efficient Method for Aldol Condensation Catalyzed by L-Lysine in Pure Water - Zhang, Yan; Wang, Man G.; Liang, Jun; Shang, Zhi Cai (Letters in Organic Chemistry, 2010)
This is a new example of a nonmetallic small-molecule catalyst for direct intermolecular aldol reactions. We found L-lysine is an effective catalyst for this condensation between unmodified acetone and a variety of aldehydes in the presence of pure water. This green catalyst system could be reused.
Keywords: L-lysine